A STUDY ON NEONATAL CARE PRACTICES IN A RURAL AREA OF BIJAPUR TALUK, BIJAPUR DISTRICT, KARNATAKA - DR. ANGADI M M; DR. BHAVANA HIREMATH; MRS.VIJAYA SORGANVI (International Journal of Pharma and Bio Sciences, 2013)
Neonatal mortality accounts for two-thirds of all infants death.Newborn care is influenced by cultural practices prevalent in an area apart from medical & economic causes. Objective: To document cultural practices prevalent in this area. Methodology: Rural community based cross – sectional study was conducted between 1st Jan 2011 to 31st March 2012. All full-term pregnant women who have delivered a live baby between 01-01-2011 to 31-12-2011 were included in the study. Information was collected in their home only after taking consent. Results: 220 post-natal mothers were interviewed. 79% were institutional deliveries. Of 220 mothers delivered, 83% wiped & covered the body before cutting the cord, 91% used a sterile cloth to clean the eyes, 98.64% used sterile instruments to cut the cord, 90% applied something to the stump of the cord, 88% babies were breastfed within1 hour, 88.64% babies were given pre-lacteal feeds, 91.8 % mothers practiced applying kajal to the eyes and putting oil in the ears. Conclusion: Though hospital deliveries,initiating breast feeding have increased, cultural practices of giving pre-lacteal feeds, putting oil in the ears, applying kajal to the eyes, have not changed much. Behavioralchanges regarding cultural practices can be brought by health education.